Does rural non-farm employment relieve or exacerbate the agricultural diversification-farm efficiency tradeoff: The case of aquaculture in Bangladesh - Abaidoo, Eric; Belton, Ben; Reardon, Thomas; Jin, Songqing; Malone, Trey (Informa UK Limited, 2025)
This paper studies how rural non-farm employment conditions the relationship between agricultural diversification and fish production efficiency. Competition for scarce productive resources typically implies a compromise between agricultural diversification and efficiency. Yet, the potential for non-farm income to resolve this tradeoff remains understudied. Cash from non-farm sources may support productivity-enhancing input purchase, thereby improving efficiency. On the other hand, by diversifying both on- and off-farm, household resources such as labor may be stretched too thin, lowering fish production efficiency. Using micro-level data on fish farming households in Southern Bangladesh, we show that at higher levels of the non-farm income share, diversification into crops results in significant allocative inefficiencies. Results are inconclusive for the technical efficiency measure.